The Role of Digital Transformation and Human Resource Competencies in Improving MSME Performance through Differentiation Strategy (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study aims to examine how digital transformation and human resource (HR) competencies influence the performance of micro, small, and medium enterprises (MSMEs) in Ungaran Regency, with differentiation strategy positioned as a mediating variable. In an ever-evolving digital landscape, MSMEs are compelled to adapt to emerging technologies while simultaneously enhancing HR capabilities to achieve optimal performance. A quantitative approach was employed in this research, with data collected through surveys and analyzed using multiple regression and path analysis techniques. The findings indicate that digital transformation has a significant positive effect on MSME performance. The adoption of digital technologies facilitates greater operational efficiency, improved customer engagement, and expanded market reach, all of which directly contribute to enhanced business outcomes. Workforce competencies also emerge as a critical factor, as the level of HR proficiency determines the extent to which MSMEs can effectively integrate and utilize digital technologies. Furthermore, differentiation strategy is found to play an essential mediating role. By implementing this strategy, MSMEs can create unique value propositions that offer competitive advantages, thereby strengthening the relationship between digital transformation, HR competencies, and business performance. The study suggests that MSMEs that invest in both digital tools and workforce development can significantly enhance their competitiveness and overall performance. This research offers practical implications for business practitioners, policymakers, and industry professionals in understanding the importance of integrating technology, human capital development, and differentiation strategies to enhance MSME success. It also opens up avenues for future research to explore additional variables that may influence MSME performance and to assess the long-term impact of digital transformation within this sector. By advancing knowledge on these critical factors, MSMEs can better navigate the challenges of the digital era and achieve sustained growth.